DO WE KNOW ALL ABOUT PREVENTION OF VENOUS THROMBOEMBOLISM AFTER MAJOR ORTHOPEDIC SURGERY? - S. A. Bozhkova (Travmatologiâ i Ortopediâ Rossii, 2018)
Venous thromboembolic events including deep venous thrombosis of lower limbs, tromboembolia of the pulmonary artery as well as non-symptomatic venous thromboembolic events are identified via venography and are considered to be potentially life-threatening implications after such major surgeries as total hip and knee arthroplasty. The need for tromboprophylaxis is well realized at present, and there is a wide range of medications with the indication of post-surgical prophylaxis of venous thromboembolic events.In this report the attempt has been made to carry out the comparative analysis of various currently used functional national guidelines on prophylaxis of venous thromboembolic events after total hip and knee arthroplasty. Moreover, having done the research in the systems PubMed (http://www.ncbi.nlm.nih.gov/pubmed, 2007–2017 гг.) and eLIBRARY (http://elibrary.ru, 2007–2017 гг.) the data of the last 10 years of experience in administration of oral anticoagulants has been collected and thoroughly analyzed (dabigatran etexilat, rivaroxaban, apixaban) and antiaggregant (acetylsalicylic acid) in clinical practice, besides comparative data has been also collected based on results obtained from laboratory control of anticoagulative effect of thrombin and x-factor direct inhibitors, even though the opportunities that laboratory control can provide are so far highly limited.At present the efficacy of pharmacological prophylaxis of venous thromboembolic events after total hip and knee arthroplasty is absolutely proven, and the issues concerning the safety of anticoagulants administration are the main focus. These issues frequently require personalized approach to selection of medication for tromboprophylaxis in accordance with the patient’s characteristics and the type of surgery chosen. All these aspects should become the focus for further research.